The Traditional Marriage Customs of the Bugis Bone in Dua Boccoe District from the Perspective of the Living Qur’an: An Analysis Based on Karl Mannheim’s Theory - Ayu Andini; Muhammad Yusuf; Rosmini; Muhammad Revi Fahrezi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study analyzes the Bugis traditional wedding customs in two subdistricts through the perspective of the Living Qur’an, using Karl Mannheim’s theory. The main objective is to understand how Bugis wedding rituals are interpreted in the context of the Qur'an and to explore the social dynamics embedded in these traditions. A qualitative approach was employee, with data collected from the head of the office of religious affairs (KUA), village imams, traditional leaders, and local community members. Data collection methods included observation, interviews, documents, and literature review. Were analyzed through reduction, presentation, and conclusion data data. the tells reveal that the bugis traditional wedding procession in dua boccoeconsists of three stages: pre marriage, marriage (akad), and post marriage. Each stage carries spiritual, social, and cultural values that remain rel evant to the bugis community. Despite some changes in the way traditions are practiced, the objectives, expressive, and documenting meaning, restingintact, aligning with mannheim's theory of ideology and utopia. Qur'anic values such as shariah, ṭahārah (Purity), and adab (Etiquette) are integrated with local culture, reinforcing t he connection between religions and traditions. This research is expected to contra st to the preservation of local traditions and Deepen the understanding of the interaction between local culture and Islamic teaching.